Anchoring task-based learning to foster cadets’ sustainable English-speaking skills - Dewi, Irma Shinta; Fatimah, Fatimah; Fauziningrum, Endah; Kritandani, Weny; Sani, Asrul (Universitas Islam Sultan Agung, 2025)
This descriptive quantitative study demonstrates that Task-Based Learning (TBL) significantly enhances the English-speaking proficiency of maritime cadets at Semarang Merchant Marine Polytechnic (SMMP). Through authentic shipboard training experiences, 30 final-year cadets showed a remarkable 16% improvement in English communication skills compared to the previous academic year. Assessment using Brown's techniques revealed robust performance in grammar (81, very good) and comprehension (79, good), with notable development in fluency (80, very good). While vocabulary (79, good) and pronunciation (78, good) showed positive results, these areas require additional focus. The instruments used in this study included recorded speaking tasks conducted during shipboard training, which were transcribed and scored using Brown’s (2004) speaking assessment rubric. Quantitative data were then analyzed using descriptive statistics to determine performance levels and identify skill-specific strengths and weaknesses. These findings highlight that integrating real-world maritime tasks with language learning creates sustainable English-speaking skills that directly enhance cadets' professional readiness. The study demonstrates that TBL effectively bridges the gap between classroom learning and industry requirements, making graduates more confident and competitive in global maritime employment.